AB0388 Results at 3 years of an optimization guideline of biological therapies in rheumatoid arthritis. create record results. (15th June 2017) - Font, P; Castro, MC; Romero, M; Ortega, R; Calvo, J; Ruiz, D; Cardenas, M; Alejandre, R; Carreto, P; Collantes, E
Abstract : Background: Dose optimization, such as dose reduction or dose spacing, is nowadays presented as a therapeutic strategy to be followed in patients with rheumatoid arthritis (RA) who have managed to reach and maintain clinical remission for a while. This strategy reduces the frequency of adverse effects and promotes cost savings Methods: Patients with RA (Criteria ACR 1987) of the CREATE registry (patients who was treated in real life conditions) who had clinical remission (DAS28 <2.6) of at least 6 months of duration on November 1, 2013, constituted the cohort of patients who were optimized for the dose received. According to the consensus of the Spanish Societies of Rheumatology and Hospital Pharmacy, the optimization of doses meant the reduction of between 20 and 50% of the same. A multidisciplinary team of rheumatologists and clinical pharmacists in a third-level hospital was involved in decision-making on treatment and dose reduction, which involved the application of protocols and the follow-up of patients at least every two months. Results: A prospective follow-up of 70 patients with RA who had received optimized doses of biological therapy for 3 years, with a mean age of 56.9 (13.7) years, of which 78.6% were women, 68.8% were positive rheumatoid factor and 66.7% ACPA +. The relapse occurred in 41.8% (at first year), 56.7% (at second year) and 62.7% (at third year). There were no statistical differences between these last 2 percentages. The median survival time of the optimization regimen was 15.24 (4.65) months (95% CI: 4.66–25.83). No statistically significant differences were found when comparing patients according to the optimized drug (antiTNF versus non-anti-TNF) (test log.rank: 0.239, p: 0.625). When relapse occurs, the patient returns to normal doses prior to optimization of the drug. Our data show that 62.7% of the patients in whom the relapse occurs at 3 years, maintains DAS28 <2, 6 (P<0.05) when dose was returned to the manufacturer recommended dose. The 37.3% (95% CI: 26.72%, 49.28%) patients maintained the optimization pattern throughout the follow-up without relapse, with an average DAS28 of 1.99 (1.07) at 3 years. Comparing these patients with those who relapse, they achieved significantly lower DAS28 values at both (p: 0.028) and at three years (p: 0.025) Conclusions: The strategy of dose reduction of biological therapies in patients with established RA that achieve sustained remission is possible in 37.3% of cases in real clinical practice (CREATE Registry) and it was maintained for 3 years. The probability of occurrence of relapse decreases after 2 years of treatment with an optimized regimen in those patients who have not relapsed before. This strategy is possible in patients with persistently controlled disease and in view of our results, it is independent of the drug administered (antiTNF versus non-antiTNF). After 3 years of follow-up, all patients maintained clinical remission (DAS 28 <2.6) despite relapses, and after resumption of the usual dose, all of them reached the therapeutic goal again. Patients who maintain clinical remission for 3 years achieve DAS28 values statistically lower than those who did not after 2 years. Disclosure of Interest: None declared